SIKAP PETANI TERHADAP PERAN PENYULUH PERTANIAN DALAM PEMBERDAYAAN USAHATANI PASCA GEMPA BUMI (THE FARMER ATTITUDE TO AGRICULTURE EXTENSION ROLE IN ENABLENESS OF AGRICULTURE EXERTION AFTER EARTHQUAKE) - Hermawan, R.; Husodo, Sapto; Agus, FX; Yulianto, Gunawan; Sulastiyah, Amie; Azhari, Hasan (Jurnal Ilmu-Ilmu Pertanian, 2007)
This research aims to know farmer's attitude of agricultural extension workers role in the region after earthquake disaster. The data were collected through a survey for farmers who were earthquake victims happened in Bantul, July 25th, 2006. To measure farmer's attitude used score. Results show that earthquake disaster caused many impact of farm. These impacts influenced farmer's attitude patterns including their attitutede's on agricultural extension workers role.